SAT0331 itnfα Agents in Refractory Non-Infectious Aortitis: Study on 19 Patients. (15th July 2016) - Fernández-Díaz, C.; Loricera, J.; Blanco, R.; Hernández, J.L.; Castañeda, S.; Humbría, A.; Melchor, S.; Collado, P.; Calvo-Catalá, J.; Rubio, E.; Rosas, J.; Ariza, R.; et al.
Abstract : Background: Non-infectious aortitis is often refractory to standard immunosuppressive therapy. In these cases, the use of inhibitors of TNF-α (iTNF-α) had been reported. Objectives: Our aim was to assess the efficacy of iTNF-α in a series of patients with refractory non-infectious aortitis. Methods: Retrospective multicenter study of patients diagnosed with aortitis refractory to traditional immunosuppressive agents and who received iTNFα. The diagnosis of aortitis was based on imaging techniques (MRI-angiography, computed tomography, PET scan, ultrasonography and/or arteriography). Results: We studied 19 patients (15 women/4 men) with a mean age of 42±13 years. The iTNFα used were: infliximab (IFX) (n=14), adalimumab (ADA) (n=3) and etanercept (ETN) (n=2). The underlying conditions were: Takayasu arteritis (TA) (n=11), giant cell arteritis (GCA) (n=2), relapsing polychondritis (RP) (n=1), ulcerative colitis (n=1), Crohn's disease (n=1), Behçet's disease (n=1), sarcoidosis (n=1) and psoriatic arthritis (n=1). Seventeen patients were previously treated with traditional immunosuppressive agents [methotrexate (MTX) (n=15), azathioprine (AZA) (n=7), cyclophosphamide (CPM) (n=5), mycophenolate mofetil (MM) (n=3), chlorambucil (n=1), cyclosporine A (n=1), tacrolimus (n=1)]. Two patients needed a switching between biologic agents (a female with TA who switched from IFX to ETN; and a male with psoriatic arthritis who switched from ETN to ADA; in both cases switching was due to inefficacy of the first biologic drug). After a median follow-up of 16 [12–36] months, most patients experienced clinical improvement, showing a reduction of erythrocyte sedimentation rate from 37.5 [30–56] mm/1st hour at baseline, to 20.5 [10–24] mm/1st hour at the last visit. Besides, C-reactive protein decreased from 1.5 [0.1- 2.6] mg/dL to 0.3 [0.1–0.8] mg/dL. After 3 months of treatment, 55% of patients had experienced clinical improvement (p<0.01); and at 12 months, clinical improvement was attained by 94% of the patients (p<0.01). A corticosteroid sparing effect was also achieved (from 25.7±22.0 mg/day of prednisone at iTNFα onset, to 6.6±5.4 mg/day at the last visit). Improvement on imaging techniques was also observed in 10 out of 13 patients (77%) who underwent a follow-up imaging procedure. Three patients had to discontinue the iTNFα agent (IFX in the 3 cases) due to inefficacy (n=1), recurrent pneumonia (n=1) and severe infusional reaction (n=1). Conclusions: iTNFα therapy appears effective and relatively safe in patients with non-infectious aortitis refractory to traditional immunosuppressive drugs. Acknowledgement: This study was supported by a grant from "Fondo de Investigaciones Sanitarias" PI12/00193 (Spain). This work was also partially supported by RETICS Programs, RD08/0075 (RIER) and RD12/0009/0013 from "Instituto de Salud Carlos III" (ISCIII) (Spain). Disclosure of Interest: None declared